Creative Writing Pedagogy: Creating an Integrated Instructional Approach based on Moseley and Lenning Taxonomy Models. - Ansari, Komal; Soomro, Shamim; Chandio, M. Tufail (International Research Journal of Art & Humanities, 2015)
The purpose of this article is to illustrate varied "learning approaches," or a broad array of learning experiences rooted in learning theory, which can be used by teachers to foster creativity in students effectively. This will include details pertaining to the developmental, cognitive and instructional learning taxonomies identified by Moseley et al. (2005a, 2005b) and supported by Lenning et al. (2013) in their research. The account will also exhibit how the mentioned learning frameworks directly correlate to the usefulness of modular teaching, and workshop model of instruction, as reliable teaching methods. Learning theories pertaining to the utilization of these models have been detailed on the grounds established by Sharples (2002) as their research setup as well. The specifics contained within this article will: • Provide ways to help other writers understand the researcher's 'thinking and working' (Sharples, 2002, p.xii). • Allow 'academics and writing researchers build up their own forms of understanding,' following an evaluative study or critique of the researcher's perspectives (ibid).